Oral Administration of Human Polyvalent IgG by Mouthwash as an Adjunctive Treatment of Chronic Oral Candidiasis - Pedraza-Sánchez, Sigifredo; Méndez-León, Julia I.; Gonzalez, Yolanda; Ventura-Ayala, María Laura; Herrera, María Teresa; Lezana-Fernández, Jose Luis; Bellanti, Joseph A.; Torres, Martha (Frontiers in Immunology, 2018)
Candida albicans is a commensal fungus that can cause disease ranging in severity from moderate to severe mucosal infections to more serious life-threating disseminated infections in severely immunocompromised hosts. Chronic mucocutaneous candidiasis (CMC) occurs in patients with mutations in genes affecting IL-17-mediated immunity, such as STAT3, AIRE, RORC, CARD9, IL12B, and IL12RB1, or gain of function (GOF) mutations in STAT1. New strategies for the treatment of candidiasis are needed because of the increased burden of infections and the emergence of drug-resistant strains. In this study, we investigated an aspect of the role of antibodies in the control of C. albicans infection. We tested in vitro the effects of C. albicans opsonization with commercial human polyvalent intravenous IgG (IV Ig) on NADPH oxidase activity and killing of the fungi by blood leukocytes from 11 healthy donors and found a significant enhancement in both phenomena that was improved by IV Ig opsonization. Then, we hypothesized that the opsonization of Candida in vivo could help its elimination by mucosal phagocytes in human patients with mucocutaneous candidiasis. We tested a novel adjunctive treatment for oral candidiasis in humans based on topical treatment with IV Ig. For this purpose, we choose two pediatric patients with well-characterized primary immunodeficiencies who are susceptible to CMC. Two eight-year-old female patients with an autosomal recessive mutation in the IL12RB1 gene (P1, with oral candidiasis) and a GOF mutation in STAT1 (P2, with severe CMC persistent since the age of eight months and resistant to pharmacological treatments) were treated with IV Ig administered daily three times a day as a mouthwash over the course of two weeks. The treatment with the IV Ig mouthwash reduced C. albicans mouth infection by 98% and 70% in P1 and P2, respectively, after 13 days, and complete fungal clearance was observed after complementary nystatin and caspofungin treatments, respectively. Therefore, treatment of oral candidiasis with human polyvalent IgG administered as a mouthwash helps eliminate mucosal infection in humans, circumventing drug resistance and opening its potential use in patients with primary or transient immunodeficiency.